Human Herpesvirus 6 Reactivation Evaluated by Digital Polymerase Chain Reaction and Its Association With Dynamics of CD134-Positive T Cells After Allogeneic Hematopoietic Stem Cell Transplantation. (7th May 2019) - Nakayama, Hitomi; Yamazaki, Rie; Kato, Jun; Koda, Yuya; Sakurai, Masatoshi; Abe, Ryohei; Watanuki, Shintaro; Sumiya, Chieko; Shiroshita, Kohei; Fujita, Shinya; Yamaguchi, Kentaro; Okamoto, Shinichiro; et al.
Abstract: Background: Human herpesvirus 6 (HHV-6) causes life-threatening central nervous system disorders after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Recent studies implicated CD134 as a specific receptor of HHV-6B and demonstrated that its expression levels in CD4-positive T cells after allo-HSCT could be related to the reactivation of HHV-6. We prospectively evaluated the relationship between HHV-6 reactivation and CD134 + T cells in the recipients of allo-HSCT. Methods: HHV-6 viral load in plasma was quantitatively measured weekly after allo-HSCT by digital polymerase chain reaction in 34 patients. The ratio of CD134 in CD4 + T cells (CD134/CD4 ratio) was serially measured by flow cytometry before and after transplantation. Results: HHV-6 reactivation was detected in 23 patients (68%). The CD134/CD4 ratio before conditioning was significantly higher in patients with HHV-6 reactivation than in those without (median, 3.8% vs 1.5%, P < .01). In multivariate analysis, a higher CD134/CD4 ratio before conditioning was significantly associated with the incidence of HHV-6 reactivation (odds ratio, 10.5 [95% confidence interval, 1.3–85.1], P = .03). Conclusions: A higher CD134/CD4 ratio before conditioning was associated with a higher risk of HHV-6 reactivation, suggesting that the rate may be a promising marker for predicting HHV-6 reactivation after allo-HSCT. Abstract : CD134/CD4 T cell ratio before transplantation was significantly associated with human herpesvirus 6 (HHV-6) reactivation after allogeneic hematopoietic stem cell transplantation detected by digital polymerase chain reaction, a novel sensitive assay.